2016
DOI: 10.14295/transportes.v24i4.1008
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação das mudanças nas velocidades das linhas de ônibus da cidade de São Paulo após a implantação de faixas exclusivas através da análise de dados de GPS

Abstract: Resumo: Este artigo apresenta uma análise da evolução das velocidades observadas nas linhas de ônibus do município de São Paulo entre os períodos de agosto de 2013 e abril de 2015. Nesse período foram implantadas faixas exclusivas para ônibus pela cidade que buscam priorizar o transporte coletivo nessas vias. Para tanto, foi desenvolvido um algoritmo que permitiu calcular as velocidades das viagens dos ônibus nas linhas através dos dados de GPS dos veículos. O algoritmo foi aplicado a um conjunto de linhas de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…The mean difference test indicated that the bus lanes increase bus speed by 9.13%. Arbex and Cunha (2016) are different from the present study because they assess the effect of the presence of bus lanes on bus speed, while we analyse the effect of the presence of bus lanes on other vehicles except buses. Paradeda, Kraus Junior and Carlson (2014) studied the effect of bus lanes in Florianopolis.…”
Section: Literature Reviewmentioning
confidence: 85%
See 3 more Smart Citations
“…The mean difference test indicated that the bus lanes increase bus speed by 9.13%. Arbex and Cunha (2016) are different from the present study because they assess the effect of the presence of bus lanes on bus speed, while we analyse the effect of the presence of bus lanes on other vehicles except buses. Paradeda, Kraus Junior and Carlson (2014) studied the effect of bus lanes in Florianopolis.…”
Section: Literature Reviewmentioning
confidence: 85%
“…Some Brazilian cities 12 already adopt a policy of corridors and bus lanes to soften the problems of urban mobility. Arbex and Cunha (2016) analysed the policy of bus lanes in São Paulo using a mean difference test. Arbex and Cunha (2016) studied the average bus speeds on streets with and without bus lanes in São Paulo over two years.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Noutro estudo, também utilizaram dados de GPS para corrigir os arquivos de GTFS para o sistema de transporte público de São Paulo e analisar a acessibilidade de cinco grandes favelas na cidade. A metodologia de transformação dos dados de GPS em dados stop_times.txt de GTFS foi detalhada em outro trabalho (Arbex e da Cunha, 2016). Nesse último trabalho, os autores propuseram uma metodologia para agregar tempos de viagens entre paradas estimados a partir de um grande período de dados arquivados de GPS.…”
Section: Revisão Da Literaturaunclassified